An application of dynamic models in evaluating relationship between direct taxes and investment in OECD countries - Kalaš, Branimir; Mirović, Vera; Milenković, Nada (Industrija, 2022)
The article researches the direct tax effect on investment share in thirty-five OECD countries for the period from 1996 to 2016 year. The goal of this research is to determine how direct taxes influence on investment level measured by the share in the gross domestic product.  The empirical analysis enables the implementation of fundamental econometric procedures as well as different dynamic panel models in order to measure effect of direct taxes. Results of Hausman show that PMG model is appropriate for measuring the effect of tax revenue growth, personal income tax, corporate income tax and property tax on investment share in selected countries. The model results reflects significant effect of tax revenue growth, personal income tax and property tax in the long term, while corporate tax is not significant for investment share in OECD countries. However, direct taxes do not have significant impact on investment share in the short-term, except tax revenue growth has positive effect on the investment in observed period.
Keywords: direct taxes, investment, dynamic modelling, OECD countries